A systematic review and meta-analysis of clinical trials on saffron (Crocus sativus) effectiveness and safety on erectile dysfunction and semen parameters - Nahid Maleki-saghooni; Khadijeh Mirzaii; Hossein Hosseinzadeh; Ramin Sadeghi; Morvarid Irani (Mashhad University of Medical Sciences, 2018)
Objective: We performed this systematic review and meta-analysis study to determine saffron (Crocus sativus) effectiveness and safety in male infertility problems. Materials and Methods: The databases PubMed, Scopus, Cochrane, Google Scholar, SID, IranMedex and Magiran until July 2016 and reference section of relevant articles, were searched to find both English and Persian clinical trials on male infertility issues that used saffron as medical treatment. Also, the quality of these trials was evaluated by Oxford Center for Evidence Based Medicine checklist. A total of six trials was ultimately included. All statistical analyses were done by Comprehensive Meta-analysis (CMA) Version 2. Results: Only in one study conducted on sperm parameters, the mean percentage of sperm with normal morphology (p